Relationship Of Tribological Property Of Different Flooring Textures On Human Mobility - Ooi, Yi Jing (Universiti Sains Malaysia, 2019)
The flooring texture is one of the major factors that contributes to slip and fall incidents. The possibility of slips and falls increases when there are liquid or aqueous present on the flooring surface. In this research, tribological property of high-gloss polished ceramics tile, normal smooth ceramic tile, structural irregular pattern ceramic tile, laminate wooden tile and vinyl tile, and effect of the presence of different liquid/ aqueous on these flooring textures were investigated, aiming for a better understanding of slip resistance property. The tribological property of these materials were being measured using pin on disc tribometer, under dry sliding and wet sliding with water, detergent solution and oil. The dynamic coefficient of friction, static coefficient of friction and specific wear rate of those flooring textures had been determined. Types of flooring textures and surface contaminants are the significant factors affecting dynamic coefficient of friction and contribute to slip recovery. Whereas sliding speed, types of flooring textures and surface contaminants are the significant factors affecting static coefficient of friction and contribute to slip initiation. Higher surface roughness of flooring textures does not give higher coefficient of friction. The coefficient of friction and specific wear rate are lower when the viscosity of surface contaminant is higher, due to squeeze film effect. During pin on disc test, adhesive wear occurred. The significant factor affecting specific wear rate is the types of flooring textures. Specific wear rate decreases when the flooring texture is harder and smoother. Finally, the tribological property of the flooring textures on human mobility from the aspect of slipperiness was ranked by plotting graph of specific wear rate against coefficient of friction. The suitable areas of application for each flooring textures were also suggested based on the ranking.